Pengembangan Tes Matematika dengan Konteks COVID-19 untuk Siswa SMP/MTs Kelas VIII - Prabowo, Anggit; Dahlan, Jarnawi Afgani (Universitas Hamzanwadi, 2020)
This study aims to develop a mathematics test with the COVID-19 context to measure the student's skill competencies in grade VIII SMP/MTs. This study was a research development by following the test development procedures: compiling blueprints, writing items, reviewing questions, testing, analyzing the results of trials, and revising. The developed test consists of multiple-choice items with four options. These items were validated content by three experts (teacher, lecturer, and mathematics trainer) and were tested to 86 students. This study developed a mathematics test set with the COVID-19 context consisting of ten items that experts declared valid. Trial of ten items showed two items (numbers 7 and 6), which were not good. Item number 7 was too easy, while item number 6 was not good in the discrimination index. Besides, the two distractors in item number 7 did not work correctly. The estimated coefficient of reliability of the measurement results was quite high, indicated by a coefficient value of 0.658. The items that were not good have been revised by modifying the items so that the index of difficulty and discrimination look good. Useful and revised items were assembled into a mathematics test set for grade VIII students.